Seismic Effects of Viscoelastic Pore Fill on Double-Porosity Rocks - Glubokovskikh, S.; Lebedev, M.; Mikhaltsevitch, Vassili; Gurevich, B. (2017)
© ASCE. We present a new model for elastic wave dispersion and attenuation in porous rocks saturated with viscous fluids and viscoelastic substances. The main idea is that the dispersion is mainly caused by frequency dependence of the normal and tangential stiffness of compliant pores that are hydraulically connected to stiff pores. First, we assume that the compliant pore (microcrack or grain-to-grain contact) is filled with an elastic solid. This allows us to obtain the stiffness of the compliant pore using a known solution of the elastic problem for a circular interlayer sandwiched between two parallel plates. The solution is then extended to viscoelastic pore fill using elastic/viscoelastic correspondence principle. The model predicts both, squirt-flow and viscous shear relaxation, and substantial increase in the rock rigidity with increasing frequency (or decreasing temperature) for rocks saturated with viscoelastic substances. The results are illustrated by an example of a typical rock saturated with water and with heavy oil.